ChemInform Abstract: A New Galloylbergenin from Bergenia crassifolia with anti‐Lipid Droplet Accumulation Activity. Issue 17 (4th April 2013) - Janar, Jenis; Fang, Liang; Wong, Chin Piow; Kaneda, Toshio; Hirasawa, Yusuke; Shahamnovna, Burasheva Gauhar; Abduahitovich, Abilov Zharylkasyn; Morita, Hiroshi
Abstract The new galloylbergenin (I) is isolated from Bergenia crassifolia together with four known related compounds.